2004
DOI: 10.1007/s00280-003-0742-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of tetrandrine, a potent inhibitor of P-glycoprotein-mediated multidrug resistance

Abstract: Multidrug resistance (MDR) is one of the main obstacles in tumor chemotherapy. A promising approach to solving this problem is to utilize a nontoxic and potent modulator able to reverse MDR, which in combination with anticancer drugs increases the anticancer effect. Experiments were carried out to examine the potential of tetrandrine (Tet) as a MDR-reversing agent. Survival of cells incubated with Tet at 2.5 micromol/l for 72 h was over 90%. Tet at 2.5 micromol/l almost completely reversed resistance to vincri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
102
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(102 citation statements)
references
References 15 publications
0
102
0
Order By: Relevance
“…IRð%Þ ¼ 1 À Mean tumor weight of experimental group Mean tumor weight of control group  100 DOX and Rho 123 accumulation assay Flow cytometry assay was performed to measure the effect of osimertinib on the intracellular accumulation of DOX and Rho 123 in cancer cells as previously described (35). Briefly, the cells were cultured in the 6-well plates and grew overnight.…”
Section: Animal Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…IRð%Þ ¼ 1 À Mean tumor weight of experimental group Mean tumor weight of control group  100 DOX and Rho 123 accumulation assay Flow cytometry assay was performed to measure the effect of osimertinib on the intracellular accumulation of DOX and Rho 123 in cancer cells as previously described (35). Briefly, the cells were cultured in the 6-well plates and grew overnight.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…We used the human non-small cell lung cancer cell line H460 and its MX-selected ABCG2-overexpressing cell line H460/MX20, the human colon carcinoma cell line S1 and its MXselected ABCG2-overexpressing cell line S1-MI-80, the human breast carcinoma cell line MCF-7 and its DOX-selected ABCB1-overexpressing cell line MCF-7/adr. Stable-transfected HEK293/ pcDNA3.1, HEK293/ABCB1, and HEK293/ABCG2 (wild-type) cells were established by selection with G418 after transfecting HEK293 with empty pcDNA3.1 vector or pcDNA3.1 vector containing full-length ABCB1 or pcDNA3.1 vector containing fulllength ABCG2 coding arginine (R) at amino acid 482 position, respectively (34)(35)(36)(37), were generous gifts from Dr. Susan Bates (NCI, NIH, Bethesda, MD). Cell lines used in this study were thawed from early passage stocks and were passaged for less than 6 months.…”
Section: Cell Lines and Cell Culturementioning
confidence: 99%
“…In vitro and in vivo studies have demonstrated that tetrandrine (Tet), a kind of herbal constituent, possesses potent and specifi c activity in reversing P-gp-mediated drug resistance (Fu et al 2004;Zhou et al 2004;Zhu et al 2005). This naturally occurring compound may be used as a chemosensitizer in the treatment of P-gp-mediated MDR malignancies (Liu et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It was mostly demonstrated that TET exerted its reversal effect through downregulating MDR1. For example, in human oral cancer MDR KBv200 cells, TET enhanced the antitumor effect of vincristine via directly binding to MDR1 and increasing intracellular VCR accumulation (29). It was even reported that TET exhibited stronger activity to reverse drug resistance to daunorubicin, vinblastine and doxorubicinin in human T lymphoblastoid leukemia MDR MOLT-4 cells, when compared to well-known MDR1 inhibitor cyclosporine A (CsA) (30).…”
Section: Discussionmentioning
confidence: 99%